2018
DOI: 10.1155/2018/4637861
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Provitamin A and Provitamin A Carotenoids as Immunomodulators: Recommended Dietary Allowance, Therapeutic Index, or Personalized Nutrition?

Abstract: Vegetables and fruits contain non-provitamin A (lycopene, lutein, and zeaxanthin) and provitamin A (β-carotene, β-cryptoxanthin, and α-carotene) carotenoids. Within these compounds, β-carotene has been extensively studied for its health benefits, but its supplementation at doses higher than recommended intakes induces adverse effects. β-Carotene is converted to retinoic acid (RA), a well-known immunomodulatory molecule. Human interventions suggest that β-carotene and lycopene at pharmacological doses affect im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(101 citation statements)
references
References 196 publications
(219 reference statements)
0
89
0
12
Order By: Relevance
“…In addition, epidemiologic studies have found a paradoxical disparity attributed to the contextual dependency of the retinoid effect. So, high plasma levels of retinoids are associated with decreased frequency of some chronic diseases Toti et al, 2018). In RA, low levels of retinoids in Fig.…”
Section: Downloaded Frommentioning
confidence: 97%
“…In addition, epidemiologic studies have found a paradoxical disparity attributed to the contextual dependency of the retinoid effect. So, high plasma levels of retinoids are associated with decreased frequency of some chronic diseases Toti et al, 2018). In RA, low levels of retinoids in Fig.…”
Section: Downloaded Frommentioning
confidence: 97%
“…In microalgae, vitamin A is mainly synthetized from the provitamin A carotenoids (e.g., β-carotene, β-cryptoxanthin, and α-carotene) [ 17 ]. The well-known β–carotene is the precursor of many carotenoids, such as those belonging to the photoprotective xanthophyll cycle (Arianna [ 13 ] and acts as antioxidant in photosynthetic organisms [ 17 ]. Indeed, the efficacy of β-carotene against the reactive oxygen species singlet oxygen is greater than vitamin E and vitamin C [ 18 ].…”
Section: Functions and Roles Of Vitamins In Microalgaementioning
confidence: 99%
“…We found in avocado both non-provitamin A (lutein and zeaxanthin) and provitamin A (β-carotene and β-cryptoxanthin) carotenoids [57] (Table 6). All carotenoids encountered have been previously identified for the fruit (see, for example, [11,20,21,23,28,29]).…”
Section: Methods Application In Real Samplesmentioning
confidence: 92%